If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) + -6 = 0 Reorder the terms: 2(1 + x) + -6 = 0 (1 * 2 + x * 2) + -6 = 0 (2 + 2x) + -6 = 0 Reorder the terms: 2 + -6 + 2x = 0 Combine like terms: 2 + -6 = -4 -4 + 2x = 0 Solving -4 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 0 + 4 2x = 0 + 4 Combine like terms: 0 + 4 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 3y+7=19 | | 2c^2=16 | | -8x+10=-6x+6 | | 17+4x-5=4(x+3) | | (3x^2-5x+4)+(x^2-4x-7)= | | 3(3x-2)-29=3x+1 | | 5a^2+13a=6 | | m^2+5m+7=0 | | 44-99x^2=0 | | 6x-(5x+8)=-4 | | 9n-3n+5= | | 6x-5x+8=-4 | | 5x+3=4(x-4) | | w^2=13w-40 | | 3r^2=-r | | 3n^2=32-4n | | y=-6x-3 | | 3(2y-7)=-2(y+1)-1 | | 32x^2-54x-5= | | -(p-8)-2(3p+5)=8-2p | | 5r^2=-8r | | 2x^2-15=-7+14x | | 3x-15=2x+10 | | 0.05h+0.4(0.8-h)=0.54+0.02h | | 16+3*5=3X | | 4r=3s | | 32x^2-32x+8=0 | | 2x-12=6x-4 | | x^2-0.6x=0.2 | | 0=-4x^2+8x-2 | | Y=-4x^2+8x-2 | | 2u+2=5u-10 |